Implementasi Metode Terbimbing Dalam Pembelajaran Hidroponik Pada Kelas Tunagrahita - Iwan Ridwan Yusup; Elsha Refina Nurannisa; Firyal Rifdah Rachman; Lestari Lestari; Nusaibah Alwafa; Pratiwi Devi Kurniasih (Politeknik Kampar, 2024)
The aim of this research is to find out how to apply or implement the guided method in hydroponic learning in mentally retarded classes. This research uses a qualitative descriptive method which is carried out by observation, interviews, and studying documents. The results of this research show that the application of guided methods in hydroponic learning in mentally retarded classes has proven to be good for improving the skills of students with special needs. This is proven by the fact that SLB students in the intellectually challenged class can plant water spinach hydroponically. Guided method with a structured approach that focuses on facilitating understanding of hydroponic concepts and developing students' practical skills in growing crops without soil. The guided method also helps students build critical skills such as problem solving, social skills, and the ability to adapt to students with special needs. In this research, it was concluded that the guided method used could help students with intellectual disabilities in hydroponic farming and train cooperation between students.